The Political Regime of Modern Israel - T. A. Karasova; M. Sterenshis (Международная аналитика, 2016)
The current research analyses the structure of the political regime in the State of Israel. It demonstrates that existing Israeli democratic institutions do not control the state’s policymaking in full, and several politically important processes are controlled or at least influenced by various other politically active forces. While these forces can influence, stimulate, inhibit, and otherwise change governmental decisions andactions, they can be labeled as kratiae. The governability of the Israeli democracy is weak, other kratiae can intervene in policymaking and the state’s regime acts as democracy-dominated multicracy.